Marine technology and sustainable development : green innovations - Olanrewaju, Oladokun Sulaiman (IGI Global, 2014)
"This book examines theoretical frameworks and empirical research in the maritime industry, evaluating new technologies, methodologies, and practices against a backdrop of sustainability"--Provided by publisher.
Keywords: Marine engineering -- Environmental aspects.; Shipping -- Environmental aspects.; Ships -- Environmental aspects.; Ships -- Energy conservation.; Green technologies -- Technological innovations.; elektronické knihy; electronic books